2009
DOI: 10.1097/phm.0b013e31817fa31d
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation and Treatment of Posterior Impingement in Dancers

Abstract: Os trigonum impingement is a frequent cause of posterior ankle pain in ballet dancers because they need extreme plantar flexion during the execution of relevé in demipointe and en pointe positions. Clinical examination and standard and modified x-rays should be carried out to clearly identify the site and entity of the impingement. If a posterior impingement is clinically diagnosed, standard and modified magnetic resonance imaging should be also performed. From September 2005 to September 2006, we considered 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 15 publications
3
38
0
2
Order By: Relevance
“…31 The most common location of tenosynovitis is within the fibrous-osseous tunnel posterior to the medial malleolus; however, it can occur along the master knot of Henry or beneath the intersesamoid ligament. [31][32][33] FHL tenosynovitis is typically ascribed to the female ballet dancers 22,34,35 ; however, it can be seen in patients with os trigonum syndrome; forceful plantarflexion activities such as soccer, downhill running, swimming, ice skating, and gymnastics; and flexor digitorum accessorius longus. [34][35][36][37][38][39][40] It is a part of the os trigonum or posterior ankle impingement syndrome.…”
Section: Flexor Hallucis Longusmentioning
confidence: 98%
See 1 more Smart Citation
“…31 The most common location of tenosynovitis is within the fibrous-osseous tunnel posterior to the medial malleolus; however, it can occur along the master knot of Henry or beneath the intersesamoid ligament. [31][32][33] FHL tenosynovitis is typically ascribed to the female ballet dancers 22,34,35 ; however, it can be seen in patients with os trigonum syndrome; forceful plantarflexion activities such as soccer, downhill running, swimming, ice skating, and gymnastics; and flexor digitorum accessorius longus. [34][35][36][37][38][39][40] It is a part of the os trigonum or posterior ankle impingement syndrome.…”
Section: Flexor Hallucis Longusmentioning
confidence: 98%
“…29 The success rate is approximately 60% to 84% after 4 to 6 months of conservative treatment as reported in the literature. 26,32,58 The success rate of corticosteroid injection varies (range, 29%-100%). 26,58,59 Temporary pain relief can delay surgery in professional or collegiate athletes 69 and confirm diagnosis as a planning step for surgical excision.…”
Section: Clinical Outcomes Os Trigonummentioning
confidence: 99%
“…Tab. 3 Beispiel einer stufenweisen Wiedereingliederung über einen Zeitraum von 6 Wochen (vereinfacht und modifi ziert nach [ 2 ] ).…”
Section: Wirtschaftlichkeitunclassified
“…V. Zwiers et al (2018) found a prevalence of 30.3 % of os trigonum in patients with no signs of posterior impingement syndrome [17]. W. Albisetti et al (2009) examined 186 young trainee ballet dancers. Twelve suffered from posterior ankle pain, and six of those (50 %) had radiologically detected os trigonum [18].…”
mentioning
confidence: 99%
“…W. Albisetti et al (2009) examined 186 young trainee ballet dancers. Twelve suffered from posterior ankle pain, and six of those (50 %) had radiologically detected os trigonum [18].…”
mentioning
confidence: 99%